Phenolic Profiles, Antioxidant Activity and Phenotypic Characterization of Lonicera caerulea L. Berries, Cultivated in Lithuania - Lina Raudonė; Mindaugas Liaudanskas; Gabrielė Vilkickytė; Darius Kviklys; Vaidotas Žvikas; Jonas Viškelis; Pranas Viškelis (MDPI AG, 2021)
Lonicera caerulea L. is an early fruit-bearing plant that originates from harsh environments. Raw materials contain a body of different phenolic origin compounds that determine the multidirectional antioxidant and pharmacological activities. The aim of this study was to comprehensively evaluate the phenolic composition, antioxidant capacities, vegetative, pomological, and sensory properties and their interrelations of selected L. caerulea cultivars, namely 'Amphora', 'Wojtek', 'Iga', 'Leningradskij Velikan', 'Nimfa', 'Indigo Gem', 'Tundra', 'Tola', and fruit powders. Combined chromatographic systems were applied for the qualitative and quantitative profiling of 23 constituents belonging to the classes of anthocyanins, flavonols, flavones, proanthocyanidins, and phenolic acids. The determined markers of phytochemical profiles were cyanidin-3-glucoside, rutin, chlorogenic, and 3,5-dicaffeoylquinic acid. Anthocyanins and the predominant compound, cyanidin-3-glucoside, were the determinants of antioxidant activity. Cultivars 'Amphora', 'Indigo Gem', and 'Tundra' contained the greatest total amounts of identified phenolic compounds. Phenotypic characterization revealed the superiority of cultivars 'Wojtek' and 'Tundra' compared to other cultivars, although 'Wojtek' had low phenolic content and antioxidant activity and 'Tundra' got lower sensory evaluation scores. Coupling the results of phenotypic and phytochemical characterization, cultivar 'Tundra' could be suitable for commercial plantations.